Molecular Characterization of Avna Library from the Flesh of Durian (Durio Zibethinus Murr.) Clone D24 - Ky, Huynh (2005)
The genus Durio is originated from Malaysia. Out of 198 registered clones, D24 is known as the best variety not only in Malaysia but also in the world. However, molecular genetic study on durian is still limited. This study was one of the initial molecular work which could contribute to the database of clone D24 durian. Firstly, we have compared three conventional methods for total RNA isolation from different types of durian tissues. The results showed that the CTAB procedure produced the best yield and high quality of total RNA from 4-month old durian flesh. The yield ranged from 75.8 pg to 272.5 pg per gram of frozen durian tissue with an average purity ratio A26dA28o0f 1.78. The RNA from 4-month old durian flesh of clone D24 was successfully used for the construction of a cDNA library. The titer of the primary cDNA library was 5.1 x106 pfulml. The percentage of recombinant plaques was 99% which indicated a sufficient cDNA library quality for full-length cDNA screening. A total of 30 randomly collected clones were generated from the cDNA library. Based on the comparison of these sequences with the GENEBANK, the sequences were classified into 7 groups according to their putative functions i.e. general metabolism (1 0 sequences); DNA and protein synthesis (4 sequences); glycosylation and transport proteins (1 sequence); respiration chain and photosynthesis (1 sequence); regulation mechanism (6 sequences); immunology (1 sequence); and novel genes (7 sequences). The initial molecular biology information of durian will also support further basic molecular work for genetic engineering and crop improvement application in the future. Consequently, two interesting clones, putative FKBP12 and quinone reductase, were subjected to further characterization. These genes were found to be present in the genome as single copy genes and expressed not only in the 4-month old durian flesh but also in other tissues such as the leaves and young flower buds. However, these genes were not found to be expressed in ripening flesh tissues. The former, FKBP12 has a main function of dissecting higher plants ca2+-dependent signal pathway. The latter, quinone reductase plays an important role in xenobiotic detoxification.